Analisis Implementasi Sistem Pengelolaan Obat Satu Pintu (One Gate Policy) Di Instalasi Farmasi Dinas Kesehatan Provinsi Bengkulu Tahun 2025 - Desi Oktavia; Tuti Rohani; Hartian Pansori (Journal Hygeia Public Health, 2026)
Intoduction: This study aims to analyze the implementation of the One Gate Policy drug management system at the Pharmaceutical Installation of the Bengkulu Provincial Health Office in 2025. The approach used is descriptive qualitative, with data collected through in-depth interviews, observations, and documentation studies. The research informants consisted of 11 individuals selected purposively, including structural officials, installation heads, and pharmacy staff directly involved in drug management.This research focuses on five main aspects of drug management: planning, procurement, storage, distribution, and usage. The results show that the One Gate Policy has brought positive changes in terms of system integration and process simplification. However, several obstacles were still found in its implementation in the field.The main challenges in implementing this policy include a lack of inter- program coordination, suboptimal utilization of digital information systems, limited human resources and infrastructure, and budget constraints, particularly for drug distribution and disposal of expired drugs. Moreover, drug usage reporting and monitoring have not been fully optimized due to the lack of awareness and understanding among staff.In conclusion, the One Gate Policy has great potential to improve the efficiency and effectiveness of drug management at the regional level. However, its success requires strengthened inter-agency coordination, continuous technical training for human resources, enhancement of logistics information systems, and adequate and sustainable budget support.